Scrub typhus leading to focal segmental glomerulosclerosis in a child due to genetic predisposition - Das, Shreyasi; Pandey, Rajendra; Roy, Sumit (International Journal of Contemporary Pediatrics, 2020)
Scrub typhus is a multisystem disease, caused by genera orientia tsutsugamushi and is currently endemic in India. In children, the disease may vary from a mild to a severe form. Complications include encephalitis, myocarditis, disseminated intravascular coagulation, acute kidney injury, atypical pneumonia, etc. The pathophysiologic mechanisms of renal involvement in scrub typhus include prerenal failure, septic shock, vasculitis, acute tubular injury and direct renal invasion by rickettsia. Here, authors present the case of a previously well 5-year old female child who was admitted to our hospital with a history of high-grade fever and pain abdomen. IgM scrub typhus turned out to be positive and she was adequately treated with doxycycline. She turned afebrile but then gradually developed anasarca, hematuria, proteinuria and persistent stage 2 hypertension. Kidney biopsy was done which revealed focal segmental glomerulosclerosis (FSGS). Further workup of the patient by whole exome sequencing revealed missense mutations in TBX18, INF2 and NPHS1 genes. Mutations in INF2 gene is a recently discovered cause of autosomal dominant FSGS. In our case, the scrub typhus mediated kidney injury probably acted as a trigger in unmasking FSGS in the already genetically susceptible child.